1989
DOI: 10.1139/x89-096
|View full text |Cite
|
Sign up to set email alerts
|

Tree-ring model interprets growth decline in natural stands of loblolly pine in the southeastern United States

Abstract: Annual ring widths and ring areas from 131 even-aged, natural, well-stocked stands of loblolly pine (Pinustaeda L.) in the Piedmont region were analyzed to reveal possible causes of a previously reported decline in radial growth. A linear aggregate model was used to separate independent factors that are known to contribute to radial growth variation in this species. Stand, site, and climatic conditions were reconstructed for each stand for the 36-year period 1949–1984 from previous inventories and from weather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

1992
1992
1998
1998

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…Reductions in radial growth during the 1970s and early 1980s for the Virginia 20/20 study are coincident in time with FIA estimates of radial growth reductions for the Virginia Coastal Plain (Fig. l), and with other loblolly pine growth declines reported in various parts of the southeast (Sheffield et al 1985;Zahner et al 1989;Ruark et al 1991;Bechtold et al 199 1;Van Deusen 1992~). Increased radial growth during the 1980s for loblolly pines (Figs.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…Reductions in radial growth during the 1970s and early 1980s for the Virginia 20/20 study are coincident in time with FIA estimates of radial growth reductions for the Virginia Coastal Plain (Fig. l), and with other loblolly pine growth declines reported in various parts of the southeast (Sheffield et al 1985;Zahner et al 1989;Ruark et al 1991;Bechtold et al 199 1;Van Deusen 1992~). Increased radial growth during the 1980s for loblolly pines (Figs.…”
Section: Discussionsupporting
confidence: 59%
“…Zahner (1963Zahner ( , 1968 found that earlywood growth is intrinsically uniform, while latewood growth is strongly regulated by the immediate, current moisture conditions. More recently, numerous studies have further quantified the effect of summer drought on decreased radial growth of loblolly pine (Cregg et al 1988;Friend and Hafley 1989;Zahner et al 1989;Jordan andLockaby 1990: Houle andDelwaide 1991) throughout most of its range.…”
Section: Droughtmentioning
confidence: 99%
See 2 more Smart Citations
“…At present, it is uncertain if the southern forests will be able to maintain (or increase) present-day levels of productivity. For example, Zahner et al, (1988) recorded a decrease hi radial growth of loblolly pine (Finns taedd) during the years from 1949 to 1984 in Piedmont stands.…”
mentioning
confidence: 99%